Blue Economy-Based City Branding Strategy for Coastal Tourism in 3T Areas (Disadvantaged, Frontier, and Outermost) - Sa'diyah El Adawiyah; Mawar; Joana Juanita Tuhumury; Abdul Rahman; Suci Lestari Handayani (Indonesian Scientific Publication, 2026)
Kupang Regency in East Nusa Tenggara (NTT) is categorized as a 3T region (Disadvantaged, Frontier, and Outermost) with substantial coastal tourism potential to support sustainable regional development. This study examines the implementation of blue economy based coastal tourism city branding in Kupang Regency using Kavaratzis’ (2004) city branding framework. The study employs a descriptive qualitative design, utilizing direct observation, in-depth interviews, and documentation. Data were collected through purposive sampling of ten key informants from relevant local government agencies, tourism related business actors, and community stakeholders. Semi structured interviews were conducted to explore branding strategies and implementation practices, and the data were analyzed using thematic coding techniques. Data credibility was ensured through triangulation of sources and methods, as well as member checking, while ethical considerations were addressed through informed consent and confidentiality assurance. The findings show that coastal tourism city branding in Kupang Regency is implemented through five interconnected stages: research, deliberation, consultation, action, and communication. The action stage is manifested in community-based ecotourism initiatives, infrastructure and accessibility improvements, and cross-sectoral stakeholder collaboration. These efforts align with the regional development vision of “Kupang Regency Towards Gold 2026” by integrating blue economy principles into coastal tourism development. This study contributes theoretically by contextualizing Kavaratzis’ city branding framework within a coastal tourism setting in 3T regions and practically by offering policy-relevant insights for sustainable tourism branding in resource-constrained areas.